Awkward Formalism: The Role of Objects in Contemporary Painting Installation - Kosovac, Ena (Auckland University of Technology, 2009)
I am a painter with a huge attachment to objects. In this painting project I aim to make objects whose objecthood is formed by the collision of the different languages of both painting and sculpture – objects that negotiate the boundary line between traditional genre divisions. These objects react to one another, where an aspect of one suggests the next, so that they develop like an epidemic. And therefore this project functions in an accumulative way, where each work or body of work acts as a stepping-stone for the next, so that the objects descend from a common ancestor and have a common origin. The project is primarily installational in nature – in the sense that, although emphasis is put on the individual objects, they are viewed together in installations, not as separate entities. I aim to consider installation in terms of the language of painting, which constitutes the formal underpinning of my practice.
Keywords: Painterly language; Sculptural language; Tinkering; Objecthood; Installation; Object